TP10.2.4Access surgery for dialysis patients during COVID-19. (28th October 2021) - Liang, Kaifeng; Lindsey, Ben; Mohammed, Ismail; Khurram, Mohammed; Sammartino, Cinzia; Sivaprakasam, Rajesh
Abstract: Aims: To describe the organisation of a triage system and COVID-19-free surgical pathway, and to assess the outcomes after its implementation for planned dialysis access surgery for patients during the first wave of the COVID-19 pandemic in the UK. Methods: In response to the suspension of elective operations due to SARS-CoV-2 outbreak, we devised a COVID-19 free surgical pathway performed in NHS and an independent hospital. We audited the outcomes of its application in patients requiring access surgery between 17 April and 15 September 2020. The data was collated, analysed, and presented at clinical governess. We are looking to re-audit for the second wave in the coming months. Results: A total of 235 cases were listed, and 203 procedures were performed. Thirty-two cases were cancelled and the top reason for cancellation was patient refusal. Of the procedures carried out, 47% (n = 96) were arteriovenous fistula formation, 42% (n = 84) were peritoneal catheter procedures, and 11% (n = 23) were arteriovenous grafts. The postoperative complication rate by day 7 was 13.3% (n = 27), by day 30 was 6.9% (n = 14) and they are similar to pre-COVID outcomes. By performing a definitive dialysis access, we avoided the significant morbidity and mortality associated with tunnel-line based dialysis. No patients acquired COVID-19 or died from its related illnesses in 30 days. Conclusion: Our results confirmed that our pathway was effective in delivering dialysis access in a timely manner and COVID safe. Our model is safe, easy to replicate COVID-19-free pathway and can be used during similar challenges in the future.